A comprehensive utilization method of ammonium sulfate waste liquid and copper-containing fluorosilicic acid waste liquid

Through the comprehensive utilization of ammonium sulfate waste liquid and copper-containing fluorosilicate waste liquid, including mixing, stripping and electrolysis, the problem of insufficient recycling of valuable components in the semiconductor industry has been solved, and efficient recycling of copper resources and production of high-value products has been achieved.

CN115747883BActive Publication Date: 2025-04-25CENTILLION ENVIRONMENT & RECYCLING (WUXI) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211658661.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-22
Publication Date
2025-04-25
Estimated Expiration
2042-12-22

AI Technical Summary

Technical Problem

The valuable components in ammonium sulfate waste liquid and copper-containing fluorosilicate waste liquid produced in the semiconductor industry cannot be efficiently recycled, resulting in waste of resources.

Method used

By mixing and stripping the ammonium sulfate waste liquid with ammonia gas, gypsum and ammonia water were obtained; then the ammonia water was electrolyzed with the copper-containing fluorosilicate waste liquid to obtain electrolytic copper and electrolytic liquid; finally, the electrolytic liquid was mixed with ammonia gas to obtain silica and ammonium fluoride, achieving efficient recovery of valuable components.

Benefits of technology

It realizes efficient recycling of copper resources in waste liquid, with high copper purity (≥99.97%) and has a high current efficiency (≥97.6%) during electrolysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115747883B_ABST
    Figure CN115747883B_ABST
Patent Text Reader

Abstract

The present invention relates to a comprehensive utilization method of ammonium sulfate waste liquid and copper-containing fluorosilicic acid waste liquid, and the comprehensive utilization method comprises the following steps: first mixing the ammonium sulfate waste liquid and ammonia, then stripping the obtained liquid phase with lime to obtain gypsum and ammonia water; second mixing the obtained ammonia water and copper-containing fluorosilicic acid waste liquid, electrolyzing the obtained mixed liquid to obtain electrolytic copper and post-electrolysis liquid; third mixing the obtained post-electrolysis liquid and ammonia to obtain silicon dioxide and ammonium fluoride. The comprehensive utilization method provided by the present invention comprehensively utilizes the ammonium sulfate waste liquid and the copper-containing fluorosilicic acid waste liquid to achieve the recovery of valuable components in the waste liquid. In the process, the ammonia component in the ammonium sulfate is recovered, and then mixed with the copper-containing fluorosilicic acid waste liquid and electrolyzed, thereby achieving efficient recovery of copper resources in the waste liquid, with high copper purity, and high current efficiency during the electrolysis process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of secondary utilization of resources, and in particular to a comprehensive utilization method of ammonium sulfate waste liquid and copper-containing fluorosilicic acid waste liquid. Background Art

[0002] Currently, in the semiconductor industry, hydrofluoric acid is usually used to etch the copper surface and treat the silicon surface to achieve the preparation of semiconductor products.

[0003] For example, CN212412002U discloses a continuous semiconductor etching device, which relates to the field of semiconductor etching equipment, including a device body, an electrical control cabinet is provided on one side of the device body, a device door is provided on the device body, glass is provided on the device door, a waste liquid collection box is provided on the bottom inner wall of the device body, and a heater is provided on the bottom inner wall of the device body. The solution provides a heater and an agitator to maintain the appropriate temperature of the etching liquid and stir the etching liquid evenly to maintain an appropriate concentration, thereby increasing the etching rate, providing two semiconductor etchings on a single line to increase the etching speed, providing a longitudinal plate and a baffle to prevent the etching liquid from splashing onto other semiconductors, providing a heating box and a fan to dry the semiconductor surface, and providing an air filter to filter impurities in the air to prevent the semiconductor from being contaminated by impurities in the air and affecting its use function.

[0004] However, a large amount of waste liquid is usually generated during the preparation process, and various methods for waste liquid are proposed in the prior art. For example, CN109368936A discloses a method for treating copper etching waste liquid, including: decomposing the copper etching waste liquid under the action of a solid filler loaded with a catalyst to obtain a first waste liquid and a first waste gas; adjusting the pH of the first waste liquid to 8-10 to obtain a second waste liquid; distilling the second waste liquid to obtain a distillate and a concentrated liquid; biochemically treating the distillate to obtain a purified liquid and a second waste gas; incinerating the concentrated liquid to obtain a third waste gas; and treating the first waste gas, the second waste gas and the third waste gas with a waste gas treatment device. The above-mentioned method for treating copper etching waste liquid can effectively control the decomposition rate of hydrogen peroxide in copper etching waste liquid, improve the safety of hydrogen peroxide decomposition, and no odor is discharged during the treatment process, and the environment will not be polluted.

[0005] As can be seen from the above, the solutions proposed in the prior art still have the problem of insufficient recovery of valuable components in the waste liquid, and some valuable components are directly processed into harmless components and discarded. Summary of the invention

[0006] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for comprehensive utilization of ammonium sulfate waste liquid and copper-containing fluorosilicic acid waste liquid, so as to solve the problem that valuable components of waste liquid generated in the semiconductor industry cannot be efficiently recovered.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] The present invention provides a comprehensive utilization method of ammonium sulfate waste liquid and copper-containing fluosilicic acid waste liquid, and the comprehensive utilization method comprises the following steps:

[0009] (1) ammonium sulfate waste liquid and ammonia gas are first mixed, and then the resulting liquid phase and lime are stripped to obtain gypsum and ammonia water;

[0010] (2) performing a second mixing of the ammonia water obtained in step (1) and the copper-containing fluorosilicic acid waste liquid, and electrolyzing the obtained mixed liquid to obtain electrolytic copper and post-electrolysis liquid;

[0011] (3) performing a third mixing of the electrolytic solution obtained in step (2) and ammonia gas to obtain silicon dioxide and ammonium fluoride;

[0012] The electrolyte used for electrolysis in step (2) contains 15-20 mg / L of chloride ions, 3-7 mg / L of polyacrylamide, and 10-13 mg / L of dodecylbenzene sulfonate.

[0013] The comprehensive utilization method provided by the present invention comprehensively utilizes ammonium sulfate waste liquid and copper-containing fluorosilicic acid waste liquid through process design, thereby realizing the recovery of valuable components in the waste liquid. During the process, the ammonia component in the ammonium sulfate is recovered, and then mixed with the copper-containing fluorosilicic acid waste liquid and then electrolyzed, thereby realizing efficient recovery of copper resources in the waste liquid, with high copper purity, and having high current efficiency during the electrolysis process.

[0014] In the present invention, the dodecylbenzene sulfonate may be sodium dodecylbenzene sulfonate and / or potassium dodecylbenzene sulfonate.

[0015] In the present invention, the electrode materials used in the electrolysis are commonly used electrode materials in the art, such as a carbon electrode for the anode and a stainless steel electrode for the cathode.

[0016] In the present invention, the chloride ion concentration in the electrolyte used for electrolysis is 15-20 mg / L, for example, it can be 15 mg / L, 15.2 mg / L, 15.4 mg / L, 15.6 mg / L, 15.8 mg / L, 16 mg / L, 16.2 mg / L, 16.4 mg / L, 16.6 mg / L, 16.8 mg / L, 17 mg / L, 17.2 mg / L, 17.4 mg / L, 17.6 mg / L, 17.8 mg / L, 18 mg / L, 18.2 mg / L, 18.4 mg / L, 18.6 mg / L, 18.8 mg / L, 19 mg / L, 19.2 mg / L, 19.4 mg / L, 19.6 mg / L, 19.8 mg / L or 20 mg / L, but is not limited to the listed values, and other unlisted values ​​within the range are equally applicable.

[0017] In the present invention, the polyacrylamide concentration in the electrolyte used for electrolysis is 3-7 mg / L, for example, it can be 3 mg / L, 3.2 mg / L, 3.4 mg / L, 3.6 mg / L, 3.8 mg / L, 4 mg / L, 4.2 mg / L, 4.4 mg / L, 4.6 mg / L, 4.8 mg / L, 5 mg / L, 5.2 mg / L, 5.4 mg / L, 5.6 mg / L, 5.8 mg / L, 6 mg / L, 6.2 mg / L, 6.4 mg / L, 6.6 mg / L, 6.8 mg / L or 8 mg / L, but is not limited to the listed values, and other values ​​not listed within the range are equally applicable.

[0018] In the present invention, the concentration of dodecylbenzene sulfonate in the electrolyte used for electrolysis is 15-20 mg / L, for example, it can be 15 mg / L, 15.2 mg / L, 15.4 mg / L, 15.6 mg / L, 15.8 mg / L, 16 mg / L, 16.2 mg / L, 16.4 mg / L, 16.6 mg / L, 16.8 mg / L, 17 mg / L, 17.2 mg / L, 17.4 mg / L, 17.6 mg / L, 17.8 mg / L, 18 mg / L, 18.2 mg / L, 18.4 mg / L, 18.6 mg / L, 18.8 mg / L, 19 mg / L, 19.2 mg / L, 19.4 mg / L, 19.6 mg / L, 19.8 mg / L or 20 mg / L, but is not limited to the listed values, and other unlisted values ​​within this range are equally applicable.

[0019] As a preferred technical solution of the present invention, the ammonium sulfate waste liquid in step (1) comprises, by mass percentage, 5-15% sulfuric acid and 20-35% ammonium sulfate.

[0020] In the present invention, the mass percentage of sulfuric acid in the ammonium sulfate waste liquid is 5-15%, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0021] In the present invention, the ammonium sulfate in the ammonium sulfate waste liquid is 20-35% by mass percentage, for example, it can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34% or 35%, etc., but is not limited to the listed values, and other unlisted values ​​within the range are equally applicable.

[0022] As a preferred technical solution of the present invention, the volume ratio of ammonium sulfate waste liquid to ammonia gas in the first mixing of step (1) is (10-20):1, for example, it can be 10:1, 10.5:1, 11:1, 11.5:1, 12:1, 12.5:1, 13:1, 13.5:1, 14:1, 14.5:1, 15:1, 15.5:1, 16:1, 16.5:1, 17:1, 17.5:1, 18:1, 18.5:1, 19:1, 19.5:1 or 20:1, but is not limited to the listed values, and other unlisted values ​​within the range are equally applicable.

[0023] As a preferred technical solution of the present invention, the liquid-to-solid ratio of the liquid phase and lime in the stripping of step (1) is (2-5):1, for example, it can be 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1, 4:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1, 4.6:1, 4.7:1, 4.8:1, 4.9:1 or 5:1, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0024] As a preferred technical solution of the present invention, the copper-containing fluorosilicic acid waste liquid in step (2) comprises, by mass percentage, 1-5% fluorocupric acid, 0.5-2% copper fluorosilicate, 10-15% fluorosilicic acid, and 5-20% hydrofluoric acid.

[0025] In the present invention, the mass percentage of fluorocupric acid in the copper-containing fluorosilicic acid waste liquid is 1-5%, for example, it can be 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8% or 5%, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0026] In the present invention, the copper fluorosilicate content in the copper-containing fluorosilicic acid waste liquid is 0.5-2% by mass, for example, it can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0027] In the present invention, the mass percentage of fluorosilicic acid in the copper-containing fluorosilicic acid waste liquid is 10-15%, for example, it can be 10%, 10.2%, 10.4%, 10.6%, 10.8%, 11%, 11.2%, 11.4%, 11.6%, 11.8%, 12%, 12.2%, 12.4%, 12.6%, 12.8%, 13%, 13.2%, 13.4%, 13.6%, 13.8%, 14%, 14.2%, 14.4%, 14.6%, 14.8% or 15%, etc., but is not limited to the listed values, and other unlisted values ​​within the range are equally applicable.

[0028] In the present invention, the mass percentage of hydrofluoric acid in the copper-containing fluorosilicic acid waste liquid is 5-20%, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0029] As a preferred technical solution of the present invention, the volume ratio of ammonia water to copper-containing fluorosilicic acid waste liquid in the second mixing of step (2) is 1:(3-5), for example, it can be 1:3, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9, 1:4, 1:4.1, 1:4.2, 1:4.3, 1:4.4, 1:4.5, 1:4.6, 1:4.7, 1:4.8, 1:4.9 or 1:5, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0030] In the present invention, the concentration of the ammonia water obtained in step (1) is 10-20%, for example, it can be 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5% or 20%, etc., but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0031] As a preferred technical solution of the present invention, the temperature of the electrolysis in step (2) is 50-75°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C or 75°C, etc., but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0032] As a preferred technical solution of the present invention, the current density of the electrolysis in step (2) is 200-300A / m 2 , for example, it can be 200A / m 2 、202A / m 2 、204A / m 2 、206A / m 2 、208A / m 2 , 210A / m 2 , 212A / m 2 , 214A / m 2 、216A / m 2 、218A / m 2 , 220A / m 2 , 222A / m 2 , 224A / m 2 、226A / m 2 , 228A / m 2 , 230A / m 2 、232A / m 2 、234A / m 2 、236A / m 2 、238A / m 2 , 240A / m 2 , 242A / m 2 、244A / m 2 、246A / m 2 、248A / m 2 , 250A / m 2 、252A / m 2 、254A / m 2 , 256A / m 2 , 258A / m 2 , 260A / m 2 、262A / m 2 , 264A / m 2 、266A / m 2 、268A / m 2 、270A / m 2 、272A / m 2 、274A / m 2 、276A / m 2 、278A / m 2 、280A / m 2 、282A / m 2 、284A / m 2 、286A / m 2 、288A / m 2 、290A / m 2 、292A / m2 、294A / m 2 、296A / m 2 、298A / m 2 or 300A / m 2 The above values ​​are not limited to the above values, and other values ​​not listed in the above values ​​are also applicable.

[0033] As a preferred technical solution of the present invention, the volume ratio of the electrolyzed liquid and the ammonia gas in the third mixture of step (3) is (8-10):1, for example, it can be 8:1, 8.1:1, 8.2:1, 8.3:1, 8.4:1, 8.5:1, 8.6:1, 8.7:1, 8.8:1, 8.9:1, 9:1, 9.1:1, 9.2:1, 9.3:1, 9.4:1, 9.5:1, 9.6:1, 9.7:1, 9.8:1, 9.9:1 or 10:1, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0034] Preferably, the ammonium fluoride in step (3) is heated and decomposed to obtain ammonium bifluoride and ammonia.

[0035] Preferably, the temperature of the thermal decomposition is 80-105°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C, 100°C, 101°C, 102°C, 103°C, 104°C or 105°C, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0036] As a preferred technical solution of the present invention, the comprehensive utilization method comprises the following steps:

[0037] (1) ammonium sulfate waste liquid and ammonia gas are first mixed, and then the resulting liquid phase and lime are stripped to obtain gypsum and ammonia water;

[0038] (2) performing a second mixing of the ammonia water obtained in step (1) and the copper-containing fluorosilicic acid waste liquid, and electrolyzing the obtained mixed liquid to obtain electrolytic copper and post-electrolysis liquid;

[0039] (3) performing a third mixing of the electrolytic solution obtained in step (2) and ammonia gas to obtain silicon dioxide and ammonium fluoride;

[0040] The ammonium sulfate waste liquid in step (1) comprises, by mass percentage, 5-15% sulfuric acid and 20-35% ammonium sulfate; the volume ratio of the ammonium sulfate waste liquid to ammonia in the first mixture is (10-20):1; the liquid-to-solid ratio of the liquid phase and lime in the stripping is (2-5):1 in mL / g;

[0041] The copper-containing fluorosilicic acid waste liquid in step (2) comprises, by mass percentage, 1-5% fluorocupric acid, 0.5-2% copper fluorosilicate, 10-15% fluorosilicic acid, and 5-20% hydrofluoric acid; the volume ratio of ammonia water to the copper-containing fluorosilicic acid waste liquid in the second mixture is 1:(3-5); the electrolyte used for the electrolysis contains 15-20 mg / L of chloride ions, 3-7 mg / L of polyacrylamide, and 10-13 mg / L of dodecylbenzene sulfonate; the temperature of the electrolysis is 50-75°C; the current density of the electrolysis is 200-300 A / m 2 ;

[0042] In step (3), the volume ratio of the electrolyzed liquid and ammonia in the third mixture is (8-10):1; the ammonium fluoride is heated and decomposed to obtain ammonium bifluoride and ammonia; the temperature of the heating and decomposition is 80-105°C.

[0043] In the present invention, the ammonia obtained in step (3) can be returned to step (1) and step (2) for use.

[0044] Compared with the prior art solutions, the present invention has the following beneficial effects:

[0045] (1) The conventional scheme of copper-containing waste acid cannot extract copper because it is highly corrosive in acidic conditions. The present method uses ammonia in ammonium sulfate for neutralization to obtain copper-ammonia complexed fluoride salts and fluorosilicates, making full use of the complexing effect of ammonium on copper to electrolyze the complexed copper. At the same time, the choice of electrode materials in alkaline conditions is expanded, providing feasibility for industrialization.

[0046] (2) The present invention utilizes the acidic waste liquid containing ammonium sulfate that is discarded after absorbing ammonia in the factory, and performs comprehensive treatment with the fluorine waste liquid after copper recovery to obtain a high-value ammonium bifluoride product, while the ammonia can be recycled again. Resource recycling is achieved at a lower carbon emission cost, and the high value of the product is ensured. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is a flow chart of a comprehensive utilization method provided by an embodiment of the present invention.

[0048] The present invention is further described in detail below. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims. DETAILED DESCRIPTION

[0049] To better illustrate the present invention and facilitate understanding of the technical solution of the present invention, typical but non-limiting embodiments of the present invention are as follows:

[0050] like Figure 1As shown, ammonium sulfate waste liquid and ammonia are mixed and stripped with lime to obtain gypsum and ammonia water. The obtained ammonia water and copper-containing fluosilicic acid waste liquid are mixed and electrolyzed to obtain electrolytic copper and post-electrolysis liquid. The post-electrolysis liquid and ammonia are mixed and ammonized to obtain silicon dioxide and ammonium fluoride. Ammonium fluoride is thermally decomposed to obtain ammonium bifluoride and ammonia. The ammonia can be returned to the above process for reuse.

[0051] Example 1

[0052] This embodiment provides a comprehensive utilization method of ammonium sulfate waste liquid and copper-containing fluorosilicic acid waste liquid, and the comprehensive utilization method comprises the following steps:

[0053] (1) ammonium sulfate waste liquid and ammonia gas are first mixed, and then the resulting liquid phase and lime are stripped to obtain gypsum and ammonia water;

[0054] (2) mixing the ammonia water (mass concentration of 14%) obtained in step (1) with the copper-containing fluorosilicic acid waste liquid for a second time, and electrolyzing the resulting mixed liquid to obtain electrolytic copper and post-electrolysis liquid;

[0055] (3) performing a third mixing of the electrolytic solution obtained in step (2) and ammonia gas to obtain silicon dioxide and ammonium fluoride;

[0056] The ammonium sulfate waste liquid in step (1) comprises, by mass percentage, 10% sulfuric acid and 27% ammonium sulfate; the volume ratio of the ammonium sulfate waste liquid to ammonia in the first mixture is 15:1; the liquid-to-solid ratio of the liquid phase to the lime in the stripping is 3.5:1 in mL / g;

[0057] The copper-containing fluorosilicic acid waste liquid in step (2) comprises, by mass percentage, 3% fluorocupric acid, 1% copper fluorosilicate, 12% fluorosilicic acid, and 12% hydrofluoric acid; the volume ratio of ammonia water to the copper-containing fluorosilicic acid waste liquid in the second mixture is 1:4; the electrolyte used for the electrolysis contains 18 mg / L chloride ions, 5 mg / L polyacrylamide, and 12 mg / L dodecylbenzene sulfonate; the temperature of the electrolysis is 57°C; the current density of the electrolysis is 250 A / m 2 ;

[0058] In step (3), the volume ratio of the electrolyzed liquid to ammonia in the third mixture is 9:1; the ammonium fluoride is heated and decomposed to obtain ammonium bifluoride and ammonia; and the temperature of the heating and decomposition is 100°C.

[0059] The product indicators are shown in Table 1.

[0060] Example 2

[0061] This embodiment provides a comprehensive utilization method of ammonium sulfate waste liquid and copper-containing fluorosilicic acid waste liquid, and the comprehensive utilization method comprises the following steps:

[0062] (1) ammonium sulfate waste liquid and ammonia gas are first mixed, and then the resulting liquid phase and lime are stripped to obtain gypsum and ammonia water;

[0063] (2) mixing the ammonia water (mass concentration of 10%) obtained in step (1) with the copper-containing fluorosilicic acid waste liquid for a second time, and electrolyzing the resulting mixed liquid to obtain electrolytic copper and post-electrolysis liquid;

[0064] (3) performing a third mixing of the electrolytic solution obtained in step (2) and ammonia gas to obtain silicon dioxide and ammonium fluoride;

[0065] The ammonium sulfate waste liquid in step (1) comprises, by mass percentage, 5% sulfuric acid and 35% ammonium sulfate; the volume ratio of the ammonium sulfate waste liquid to ammonia in the first mixture is 10:1; the liquid-to-solid ratio of the liquid phase to the lime in the stripping is 5:1 in mL / g;

[0066] The copper-containing fluorosilicic acid waste liquid in step (2) comprises, by mass percentage, 5% fluorocopper acid, 2% copper fluorosilicate, 10% fluorosilicic acid, and 5% hydrofluoric acid; the volume ratio of ammonia water to the copper-containing fluorosilicic acid waste liquid in the second mixture is 1:5; the electrolyte used for the electrolysis contains 20 mg / L chloride ions, 7 mg / L polyacrylamide, and 13 mg / L dodecylbenzene sulfonate; the temperature of the electrolysis is 50°C; the current density of the electrolysis is 300A / m 2 ;

[0067] In step (3), the volume ratio of the electrolyzed liquid to ammonia in the third mixture is 8:1; the ammonium fluoride is heated and decomposed to obtain ammonium bifluoride and ammonia; the temperature of the heating and decomposition is 105°C.

[0068] The product indicators are shown in Table 1.

[0069] Example 3

[0070] This embodiment provides a comprehensive utilization method of ammonium sulfate waste liquid and copper-containing fluorosilicic acid waste liquid, and the comprehensive utilization method comprises the following steps:

[0071] (1) ammonium sulfate waste liquid and ammonia gas are first mixed, and then the resulting liquid phase and lime are stripped to obtain gypsum and ammonia water;

[0072] (2) mixing the ammonia water (mass concentration of 20%) obtained in step (1) with the copper-containing fluorosilicic acid waste liquid for a second time, and electrolyzing the resulting mixed liquid to obtain electrolytic copper and post-electrolysis liquid;

[0073] (3) performing a third mixing of the electrolytic solution obtained in step (2) and ammonia gas to obtain silicon dioxide and ammonium fluoride;

[0074] The ammonium sulfate waste liquid in step (1) comprises, by mass percentage, 15% sulfuric acid and 20% ammonium sulfate; the volume ratio of the ammonium sulfate waste liquid to ammonia in the first mixture is 20:1; the liquid-to-solid ratio of the liquid phase to the lime in the stripping is 2:1 in mL / g;

[0075] The copper-containing fluorosilicic acid waste liquid in step (2) comprises, by mass percentage, 1% fluorocupric acid, 0.5% copper fluorosilicate, 15% fluorosilicic acid, and 20% hydrofluoric acid; the volume ratio of ammonia water to the copper-containing fluorosilicic acid waste liquid in the second mixture is 1:3; the electrolyte used for the electrolysis contains 15 mg / L chloride ions, 3 mg / L polyacrylamide, and 10 mg / L dodecylbenzene sulfonate; the temperature of the electrolysis is 75°C; the current density of the electrolysis is 200 A / m 2 ;

[0076] In step (3), the volume ratio of the electrolyzed liquid to ammonia in the third mixture is 10:1; the ammonium fluoride is heated and decomposed to obtain ammonium bifluoride and ammonia; and the temperature of the heating and decomposition is 80°C.

[0077] The product indicators are shown in Table 1.

[0078] Example 4

[0079] This embodiment provides a comprehensive utilization method of ammonium sulfate waste liquid and copper-containing fluorosilicic acid waste liquid, and the comprehensive utilization method comprises the following steps:

[0080] (1) ammonium sulfate waste liquid and ammonia gas are first mixed, and then the resulting liquid phase and lime are stripped to obtain gypsum and ammonia water;

[0081] (2) mixing the ammonia water (mass concentration of 17%) obtained in step (1) with the copper-containing fluorosilicic acid waste liquid for a second time, and electrolyzing the resulting mixed liquid to obtain electrolytic copper and post-electrolysis liquid;

[0082] (3) performing a third mixing of the electrolytic solution obtained in step (2) and ammonia gas to obtain silicon dioxide and ammonium fluoride;

[0083] The ammonium sulfate waste liquid in step (1) comprises, by mass percentage, 12% sulfuric acid and 30% ammonium sulfate; the volume ratio of the ammonium sulfate waste liquid to ammonia in the first mixture is 18:1; the liquid-to-solid ratio of the liquid phase to the lime in the stripping is 3:1 in mL / g;

[0084] The copper-containing fluorosilicic acid waste liquid in step (2) comprises, by mass percentage, 4% fluorocupric acid, 1.5% copper fluorosilicate, 14% fluorosilicic acid, and 17% hydrofluoric acid; the volume ratio of ammonia water to the copper-containing fluorosilicic acid waste liquid in the second mixture is 1:3.4; the electrolyte used for the electrolysis contains 15 mg / L chloride ions, 4 mg / L polyacrylamide, and 11 mg / L dodecylbenzene sulfonate; the temperature of the electrolysis is 65°C; the current density of the electrolysis is 240 A / m 2 ;

[0085] In step (3), the volume ratio of the electrolyzed liquid to ammonia in the third mixture is 8.5:1; the ammonium fluoride is heated and decomposed to obtain ammonium bifluoride and ammonia; and the temperature of the heating and decomposition is 90°C.

[0086] The product indicators are shown in Table 1.

[0087] Example 5

[0088] The only difference from Example 1 is that step (1) is not performed and the ammonia water in step (2) is directly replaced by an equal amount of ammonium sulfate waste liquid in step (1). The indexes of the obtained product are shown in Table 1.

[0089] Example 6

[0090] The only difference from Example 1 is that polyacrylamide is not added to the electrolyte used in the electrolysis. The indexes of the obtained product are shown in Table 1.

[0091] Example 7

[0092] The only difference from Example 1 is that sodium dodecylbenzene sulfonate is not added to the electrolyte used in the electrolysis. The indexes of the obtained product are shown in Table 1.

[0093] Example 8

[0094] The only difference from Example 1 is that the chloride ion concentration of the electrolyte used in the electrolysis is 30 mg / L. The indexes of the obtained product are shown in Table 1.

[0095] Example 9

[0096] The only difference from Example 1 is that the polyacrylamide concentration of the electrolyte used in the electrolysis is 10 mg / L. The indexes of the obtained product are shown in Table 1.

[0097] Example 10

[0098] The only difference from Example 1 is that the concentration of sodium dodecylbenzene sulfonate in the electrolyte used in the electrolysis is 20 mg / L. The indexes of the obtained product are shown in Table 1.

[0099] In the above embodiments, the anode used for electrolysis is a carbon electrode, and the cathode is stainless steel.

[0100] Table 1

[0101] Current efficiency / % Electrolytic copper purity / % Example 1 98.7 99.98 Example 2 97.6 99.99 Example 3 98.2 99.97 Example 4 97.8 99.98 Example 5 88.5 99.23 Example 6 89.6 99.34 Example 7 87.6 99.53 Example 8 85.6 99.43 Example 9 83.3 99.38 Example 10 86.6 99.66

[0102] It can be seen from the results of the above embodiments that the comprehensive utilization method provided by the present invention, through the design of the process, comprehensively utilizes ammonium sulfate waste liquid and copper-containing fluorosilicic acid waste liquid to achieve the recovery of valuable components in the waste liquid. During the process, the ammonia component in the ammonium sulfate is recovered and then mixed with the copper-containing fluorosilicic acid waste liquid for electrolysis, thereby achieving efficient recovery of copper resources in the waste liquid, with high copper purity (≥99.97%), and having a high current efficiency (≥97.6%) during the electrolysis process.

[0103] It is stated that the present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0104] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0105] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0106] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for comprehensive utilization of ammonium sulfate waste liquid and copper-containing fluorosilicic acid waste liquid, characterized in that: The comprehensive utilization method comprises the following steps: (1) ammonium sulfate waste liquid and ammonia gas are first mixed, and then the resulting liquid phase and lime are stripped to obtain gypsum and ammonia water; (2) performing a second mixing of the ammonia water obtained in step (1) and the copper-containing fluorosilicic acid waste liquid, and electrolyzing the obtained mixed liquid to obtain electrolytic copper and post-electrolysis liquid; (3) performing a third mixing of the electrolytic solution obtained in step (2) and ammonia gas to obtain silicon dioxide and ammonium fluoride; The electrolyte used for electrolysis in step (2) contains 15-20 mg / L of chloride ions, 3-7 mg / L of polyacrylamide, and 10-13 mg / L of dodecylbenzene sulfonate.

2. The comprehensive utilization method according to claim 1, characterized in that: The ammonium sulfate waste liquid in step (1) comprises, by mass percentage, 5-15% sulfuric acid and 20-35% ammonium sulfate.

3. The comprehensive utilization method according to claim 1 or 2, characterized in that: In step (1), the volume ratio of ammonium sulfate waste liquid to ammonia gas in the first mixture is (10-20):

1.

4. The comprehensive utilization method according to claim 1, characterized in that: The liquid-to-solid ratio of the liquid phase and lime in the stripping step (1) is (2-5):1 in mL / g.

5. The comprehensive utilization method according to claim 1, characterized in that: The copper-containing fluorosilicic acid waste liquid in step (2) comprises, by mass percentage, 1-5% fluorocupric acid, 0.5-2% copper fluorosilicate, 10-15% fluorosilicic acid, and 5-20% hydrofluoric acid.

6. The comprehensive utilization method according to claim 1, characterized in that: In step (2), the volume ratio of ammonia water to copper-containing fluorosilicic acid waste liquid in the second mixing is 1:(3-5).

7. The comprehensive utilization method according to claim 1, characterized in that: The temperature of the electrolysis in step (2) is 50-75°C.

8. The comprehensive utilization method according to claim 1, characterized in that: The current density of the electrolysis in step (2) is 200-300A / m 2 .

9. The comprehensive utilization method according to claim 1, characterized in that: The volume ratio of the electrolyzed liquid and ammonia gas in the third mixture of step (3) is (8-10):

1.

10. The comprehensive utilization method according to claim 1, characterized in that: The ammonium fluoride in step (3) is heated and decomposed to obtain ammonium bifluoride and ammonia.

11. The comprehensive utilization method according to claim 10, characterized in that: The temperature of the heating decomposition is 80-105°C.

12. The comprehensive utilization method according to claim 1, characterized in that: The comprehensive utilization method comprises the following steps: (1) ammonium sulfate waste liquid and ammonia gas are first mixed, and then the resulting liquid phase and lime are stripped to obtain gypsum and ammonia water; (2) performing a second mixing of the ammonia water obtained in step (1) and the copper-containing fluorosilicic acid waste liquid, and electrolyzing the obtained mixed liquid to obtain electrolytic copper and post-electrolysis liquid; (3) performing a third mixing of the electrolytic solution obtained in step (2) and ammonia gas to obtain silicon dioxide and ammonium fluoride; The ammonium sulfate waste liquid in step (1) comprises, by mass percentage, 5-15% sulfuric acid and 20-35% ammonium sulfate; the volume ratio of the ammonium sulfate waste liquid to ammonia in the first mixture is (10-20):1; the liquid-to-solid ratio of the liquid phase and lime in the stripping is (2-5):1 in mL / g; The copper-containing fluorosilicic acid waste liquid in step (2) comprises, by mass percentage, 1-5% fluorocupric acid, 0.5-2% copper fluorosilicate, 10-15% fluorosilicic acid, and 5-20% hydrofluoric acid; the volume ratio of ammonia water to the copper-containing fluorosilicic acid waste liquid in the second mixture is 1:(3-5); the electrolyte used for the electrolysis contains 15-20 mg / L of chloride ions, 3-7 mg / L of polyacrylamide, and 10-13 mg / L of dodecylbenzene sulfonate; the temperature of the electrolysis is 50-75°C; the current density of the electrolysis is 200-300 A / m 2 ; In step (3), the volume ratio of the electrolyzed liquid and ammonia in the third mixture is (8-10):1; the ammonium fluoride is heated and decomposed to obtain ammonium bifluoride and ammonia; the temperature of the heating and decomposition is 80-105°C.

Citation Information

Patent Citations

  • Treatment method of copper etching waste liquid

    CN109368936A

  • A continuous semiconductor etching apparatus is provided

    CN212412002U

  • Method for recycling hydrofluoric acid from wastewater containing fluorosilicic acid

    CN106185817A

  • Method for resource utilization of etching process waste

    CN113023749A